Technical details and long-term outcomes of P.A.D.U.A. for congenital urethral narrowing; a case series and review of the literature. Issue 1 (February 2023) - Danzig, Matthew R.; Kryger, John V.; Groth, Travis W.; Roth, Elizabeth B.; Ellison, Jonathan S.
Summary: Introduction: The P.A.D.U.A. technique is a method of addressing congenital urethral narrowing. It involves passive dilation with a series of progressively larger indwelling catheters. Utilization is limited by scant literature, particularly regarding technical details and long-term durability. Tools for achieving safe and reliable urinary drainage are critical in these patients, who require careful stewardship of their kidney and bladder function. Objective: To describe long-term urethral patency and urinary function following P.A.D.U.A., and to provide sufficient technical detail to reproduce the technique. Study design: Patients with congenital urethral narrowing managed with P.A.D.U.A. were identified and chart review was performed. Details of catheter exchange sequences were compiled and described. The primary outcome was the attainment of adequate urethral caliber by successful completion of P.A.D.U.A., and the secondary outcome was voiding per urethra at most recent follow-up. Results: P.A.D.U.A. achieved adequate urethral caliber in 9/11 (82%) of patients. This included seven patients with Prune Belly Syndrome, one with isolated urethral atresia, and one with a cloacal anomaly. P.A.D.U.A. failed to achieve urethral patency in one patient with urethral duplication, who was unable to progress through the catheter sequence, and one patient with Prune Belly Syndrome, who completed P.A.D.U.A. but developed recurrent narrowing one week later. There were no delayed failures of urethral patency. Patients who achieved patency underwent a median of seven catheter placements over 92 days. Median (range) initial and final catheter sizes were 3.5F (1.9–8F) and 14F (8–16F). While 82% achieved patency, only 3/11 (27%) were voiding spontaneously per native urethra at most recent follow-up. Discussion: This series of patients undergoing P.A.D.U.A. for primary treatment of congenital urethral narrowing is the largest to date and provides granular technical details. It aligns with prior reports suggesting that P.A.D.U.A. achieves urethral patency in most patients with Prune Belly Syndrome or isolated urethral atresia, but has limited application in the hypoplastic duplicated urethra. Despite high rates of urethral patency in this select population, many patients will not achieve and maintain spontaneous voiding without catheterization. This is likely due to ongoing deterioration of bladder function caused by the prenatal developmental insult, paralleling the phenomenon seen in posterior urethral valves. Conclusion: P.A.D.U.A. is an effective and durable technique for achieving urethral patency. However, due to complicating factors such as the underlying bladder pathology present in many patients, urethral patency achieved with P.A.D.U.A. does not guarantee long-term safe and reliable spontaneous emptying per urethra. Summary Figure Current urinary status . Voiding status as of most recent follow-up for all patients in the cohort. Summary Figure